Disability People: AbilityFin / Elhan Marzuki … [et al.] - Marzuki, Elhan; Mohamed Hanapi, Halme Hakemie; Abdullah, Amirah Fakhira; Mohd Azmy, Fify Ashaqiera; Shahrulnizam, Nuralia Nabihah; Salimin, Nur Fitrialia; Hassian, Ummi Kalsum (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
AbilityFin is a groundbreaking tool that enhances the banking experience for visually impaired individuals. AbilityFin, which is integrated into online banking platforms, offers special budgeting options to blind customers. AbilityFin's voice command features allow visually impaired persons to properly manage their money and attain financial independence. This abstract focuses on AbilityFin's core characteristics, specifically accessibility, security, and privacy. By adopting AbilityFin, financial institutions encourage inclusion and equal opportunity for visually impaired people, improving the banking experience and empowering blind customers.